Experimental and Theoretical Analysis of Ink Dispersion Stability for Polymer Electrolyte Fuel Cell Applications. Issue 6 (4th April 2017) - Shukla, S.; Bhattacharjee, S.; Weber, A. Z.; Secanell, M.
Abstract : The aggregate size in fuel cell catalyst inks depends on the type of dispersion medium, particle concentration, and addition of stabilizing agents. In this work, ink stability and particle size of carbon black and carbon black/Nafion dispersions in four non-aqueous media, viz., methanol, ethanol, isopropanol and ethyl acetate are studied. Based on visual inspection, isopropanol is found to be the best medium for dispersion of carbon black inks. To rationalize this observation, a semi-empirical model based on diffusion-limited aggregation was developed to evaluate the rate of particle aggregation and predict the ink stability time for each dispersion medium. The proposed model supports the experimental observation by qualitatively predicting the same relationship between carbon stability and the dispersion media. The model also showed that the dielectric constant of the dispersion medium and the particle zeta potential are primarily responsible for the ink stability. Particle size for the different inks was determined by dynamic light scattering with and without dilution. Experimental results show that Nafion is a strong stabilizing agent, increasing the ink stability and decreasing the particle size of carbon aggregates. The beneficial effects of Nafion are independent of its concentration and are observed even at Nafion volume fractions of 10 wt%. The interaction energy is found to be a strong function of the surface potential for the dispersion medium with a higher dielectric constant.